2022
DOI: 10.1101/2022.03.30.22273165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of COVID-19 vaccination on menstrual periods in a prospectively recruited cohort

Abstract: COVID-19 vaccination protects against the potentially serious consequences of SARS-CoV2 infection, but some people have been hesitant to receive the vaccine because of reports that it could affect menstrual bleeding. To determine whether this occurs, we prospectively recruited a cohort of 79 individuals, each of whom recorded details of at least three consecutive menstrual cycles, during which time they each received at least one dose of COVID-19 vaccine. We find that either dose of the COVID-19 vaccine is ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The current study estimates that there is abnormal uterine bleeding after vaccination in almost one-third of vaccinated females. Individual studies also report that this is transient and mild [31][32][33][34][35][36]. The current analysis found no speci c vaccine manufacturer to in uence the abnormal bleeding rate.…”
Section: Strength and Limitationsmentioning
confidence: 56%
See 1 more Smart Citation
“…The current study estimates that there is abnormal uterine bleeding after vaccination in almost one-third of vaccinated females. Individual studies also report that this is transient and mild [31][32][33][34][35][36]. The current analysis found no speci c vaccine manufacturer to in uence the abnormal bleeding rate.…”
Section: Strength and Limitationsmentioning
confidence: 56%
“…Emerging evidence suggests that abnormal uterine bleeding is short lasting, not requiring treatment or hospitalization [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Nevertheless, abnormal uterine bleeding disrupts daily tasks, hindering normal activities and inducing associated stress.…”
Section: Introductionmentioning
confidence: 99%
“…A link between COVID-19 vaccination and menstruation is biologically plausible. Although one retrospective study (published as a preprint) examining menstrual cycle records did not detect a link between COVID-19 vaccination and menstrual changes, 5 a study using prospectively tracked menstrual cycle data showed that COVID-19 vaccination is associated with a less than 1-day increase in menstrual cycle length. 12 The process of menstruation, in which endometrial tissue proliferates and breaks down in the absence of egg fertilisation and implantation, is regulated by complex interactions between hormones, inflammation pathways, tissues, and cells.…”
Section: Discussionmentioning
confidence: 97%
“…There have been reports about menstrual irregularities and vaginal bleeding occurring after COVID-19 vaccination in social and traditional media, the Vaccine Adverse Event Reporting System, vaccine monitoring systems in the UK and Norway, and online surveys. 5 , 6 , 7 , 8 , 9 Symptoms related to menstruation and vaginal bleeding were not solicited adverse events in clinical trials of COVID-19 vaccines, and they were not solicited as prespecified symptoms in v-safe, a voluntary active surveillance system monitoring health status after COVID-19 vaccination in the USA. 10 In August, 2021, the National Institutes of Health announced funding of research studies exploring potential links between COVID-19 vaccination and menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in various countries have suggested potential associations between COVID-19 vaccination and menstrual changes. For instance, several studies have reported an increased prevalence of menstrual irregularities and changes in menstrual patterns, such as alterations in cycle length and flow volume, following COVID-19 vaccination [8][9][10][11][12][13]. However, these studies were conducted in different settings and populations.…”
Section: Introductionmentioning
confidence: 99%